A study of promotion and assessment policies with particular reference to the transitional period in South Africa - Van der Westhuizen, A. C.(Andre Cornelius) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1996.